2007
DOI: 10.5371/jkhs.2007.19.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Methods to Increase the Effectiveness of Trochanteric Stabilizing Plate for Unstable Femoral Intertrochanteric Fractures with Gtreater Trochanteric Fracture - Fixation of Greater Trochanter with Wire and Screw -

Abstract: The clinical outcome is favorable for the treatment of unstable femoral intertrochanteric fractures using both dynamic hip screw (DHS) and trochanter stabilizing plate (TSP) in elderly patients. However, there are sometimes complications related to excessive sliding. Therefore, the aim of this study was to evaluate the value of additional fixation of greater trochanter using wires and screw in the unstable femoral intertrochanteric fractures with a greater trochanter fracture. Materials and Methods: From March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The fractures of the greater trochanter involving the vastus ridge were not type A2 but type A3, which were not covered in this study. Some reported that this posterior fracture fragment can be fixed with screws to increase the stability, but we could reduce and fix this as well as the posteromedial bone fragment with one cerclage wiring alone 15). The fractured greater trochanteric fragment not involving the vastus ridge could also be supported with the addition of a TSP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fractures of the greater trochanter involving the vastus ridge were not type A2 but type A3, which were not covered in this study. Some reported that this posterior fracture fragment can be fixed with screws to increase the stability, but we could reduce and fix this as well as the posteromedial bone fragment with one cerclage wiring alone 15). The fractured greater trochanteric fragment not involving the vastus ridge could also be supported with the addition of a TSP.…”
Section: Discussionmentioning
confidence: 99%
“…In both groups, an antirotation screw was also inserted for additional stability. A cancellous screw used parallel to the lag screw was reported to be helpful in preventing rotation of the femoral head portion in the early weight bearing period 15). This antirotation screw was used in twenty one cases (group I-III).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation